A study of college students’ perceptions of utilizing automatic speech recognition technology to assist English oral proficiency - Liu, Jiaxin; Liu, Xianghu; Yang, Chuan (Frontiers in Psychology, 2022)
For EFL (English as a Foreign Language) students, automatic speech recognition (ASR) technology is the most potential assisting tool to help them improve their English oral proficiency. This study aims to investigate learners’ perceptions towards ASR technology after it is applied to traditional classrooms. The number of the research participants was 249 students majoring in English from a university in northeast China and they were divided into an experimental group consisting of 124 students and a control group including 125 students. The two groups used ASR technology in the process of oral practice, and the experimental group also added teacher’s guidance, compared with the control group. The data of two questionnaires were collected before and after the experiment as well as the data of the reflective learning journals obtained during the study. The results of this study indicated that the participants held positive and satisfactory attitudes towards the potential of ASR technology in oral training and they also believed that the technology could meet many of their needs such as the scoring system to help them more intuitively understand the real speaking level as well as improve their speaking ability. In terms of the recognition accuracy of ASR technology, the participants also suggested that technological innovations should be increased in order to meet the demands of language learners for improving oral proficiency. It is expected that the research results will offer language teachers enlightenments to the enhancement of the oral English teaching quality in the future.